2017
DOI: 10.19080/aibm.2017.04.555633
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Extracellular Collagenase from Pseudomonas sp: Remarkable Collagenolytic Activity

Abstract: A collagenase from Pseudomonas sp. was purified upto 13-fold with a yield of 3.6% using hydrophobic interaction chromatography. Molecular weight of 34kDa collagenase was identified using sodium dodecyl sulfate-polyacrylamide gel electrophoresis method. Gelatin and collagen substrates were used in the characterization of purified collagenase. The optimum temperature and pH were 45 °C, pH 7.5 for gelatin and 50 °C, pH 8.5 for collagen respectively. The collagenase activity was highly inhibited by Hg2+, Pb2+, EDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The shift of optimum pH was attributed to the electrostatic interaction influenced by the carrier microenvironment. The results of this study was compatible with the results mentioned by Gautam et al (15), they found that the optimum pH of collagenase activity purified from S. aureus was 7.0. Effect of temperature on collagenase activity: The activity of partial pure collagenase was measured at temperatures ranging from 25°C to 60°C.…”
Section: Characterization Of Collagenase Effect Of Ph On Collagenase ...supporting
confidence: 93%
“…The shift of optimum pH was attributed to the electrostatic interaction influenced by the carrier microenvironment. The results of this study was compatible with the results mentioned by Gautam et al (15), they found that the optimum pH of collagenase activity purified from S. aureus was 7.0. Effect of temperature on collagenase activity: The activity of partial pure collagenase was measured at temperatures ranging from 25°C to 60°C.…”
Section: Characterization Of Collagenase Effect Of Ph On Collagenase ...supporting
confidence: 93%
“…Moreover, Yasmin et al [1] reported that IAA producing PGPR enhanced the nutrients uptake through modulating the root architecture in the drought stressed soil. Thus, PGPB can serve as a phytostimulator but potential traits of the PGPB can be altered genetically by different environmental stresses [5]. Consortium of newly isolated and already characterized PGPR will ensure their sustainable use in crop production [6].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, under such conditions the bacterial cell membrane easily transports these ions into the cell and changes its osmotic pressure, which can affect the viability of the bacteria. Researchers have noticed that the activity of P. aeruginosa JCM5962 (T) enzymes and other species of Pseudomonas decreases when the medium has a high Na + ion concentration (Gautam and Azmi 2017;Sachan et al 2017). strategy of adding inoculum progressively was effective in improving the fermentation process.…”
Section: Resultsmentioning
confidence: 99%